2015
DOI: 10.1515/pjvs-2015-0046
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone-induced changes in the lymphoid tissue and mucosal nerve fibers in the porcine ileum

Abstract: This is the first study to examine zearalenone-(ZEN) induced changes in the immune system of the ileum and substance P-(SP-) and vasoactive intestinal peptide-(VIP-) immunoreactive nerve fibers in the mucosa, which participate in the regulation of intestinal functions under physiological conditions and during pathological processes. The aim of this study was also to identify potential relationships between selected immune and neural elements in ileal Peyer's patches in pigs that were and were not exposed to ZE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…Two facts confirm this supposition. Firstly, it is well known that the expression of neuroprotective factors in the ENS increases during pathological processes [5,6,42,43], and the growth of CGRP-like immunoreactivity has been observed during both the present study and in previous investigations on other fragments of the digestive tract [44]. Secondly, CGRP affects the release of nitric oxide, whose neuroprotective activity is relatively well surveyed [45,46,47].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Two facts confirm this supposition. Firstly, it is well known that the expression of neuroprotective factors in the ENS increases during pathological processes [5,6,42,43], and the growth of CGRP-like immunoreactivity has been observed during both the present study and in previous investigations on other fragments of the digestive tract [44]. Secondly, CGRP affects the release of nitric oxide, whose neuroprotective activity is relatively well surveyed [45,46,47].…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, it can lead to developmental disorders, stunted growth, renal failure, and blood clots [4,5]. ZEN also harms the digestive system by causing cell proliferation and inflammation of the intestinal mucosal layer [5,6]. Previous studies have also shown the negative effects of ZEN on the nervous system, which are related to the presence of estrogen receptors in the brain and the fact that phytoestrogens are able to cross the blood-brain barrier [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors, this is the first report demonstrating that ZEN affects nerve fibres in the digestive tract at low dose. Obremski et al (2015a) fed prepubertal gilts (aged 2 months) with diets containing 0.1 mg ZEN/kg feed in gelatine capsules for 42 days (corresponding to a dose of 5 lg ZEN/kg bw per day). After that, ileal Peyer's patch (IPP) samples were prepared and used for analyses.…”
Section: Pigsmentioning
confidence: 99%
“…It is known that the oesophagus may receive innervation from jugularnodose, sphenopalatine, stellate and dorsal root ganglia (Yu et al, 2015), but the major adrenergic innervation of this part of the GI tract derives from the superior cervical ganglia (Wojtkiewicz et al, 2011;Juranek and Wojtkiewicz, 2015). To date, a wide range of active substances have been noted both in the ENS and extrinsic innervation (Majewski et al, 2002;Obremski et al, 2015;Rytel and Calka, 2016;Szymanska et al, 2018), including neuropeptide Y (NPY).…”
mentioning
confidence: 99%